Optimum growth and carbon policies with lags in the climate system - Bretschger, Lucas; Karydas, Christos (Oxford, 2014)
"We study the eects of greenhouse gas emissions on optimum growth and climate policy by using an endogenous growth model with polluting non-renewable resources. Climate change harms the capital stock. Our main contribution is to introduce and extensively explore the naturally determined time lag between greenhouse gas emission and the damages due to climate change, which proves to be crucial for the transition of the economy towards its steady state. The social optimum and the optimal abatement policies are fully characterized. The inclusion of a green technology delays optimal resource extraction.The optimal tax rate on emissions is proportional to output. Poor understanding of the emissions diffusion process leads to suboptimal carbon taxes and suboptimal growth and resource extraction."